Green synthesis of copper nanoparticle using ionic liquid-based extraction from Polygonum minus and their applications - Ullah, H. (Taylor and Francis Ltd., 2019)
The present work reports the extraction of phenolic compounds from Polygonum minus using ionic liquid as extracting solvent. In this work, 1-Butyl-3-methylimidazolium hydrogen sulfate BMIMHSO4 was used for the extraction of bioactive compounds. Accordingly, ionic liquids based microwave-assisted extraction treatment for separating of bioactive compounds from polygonum minus was first performed in the present study. The results obtained in this work have high extraction yield in comparison with conventional solvent. UV/Vis results showed that microwave synthesis was fast, well dispersed and nanosized copper nanoparticle (CuNPs) in comparison with conventional synthesis. CuNPs was characterised by X-Rays diffractometer (XRD), Fourier transform infrared (FTIR), dynamic light scattering (DLS), field emission scanning electron microscopy combined with energy dispersive x-rays (FESEM-EDX), and thermogravimetric analysis (TGA). All the instrumental analyses confirmed the particles were nanosized. Furthermore, the antibacterial activity of as-synthesised CuNPs showed effective inhibitory zone against three different bacteria. The photocatalytic degradation of copper nanoparticles was studied using methylene blue (MB) and methyl orange (MO) dyes under UV light and degraded 99.9% within short time 8 and 7 min. Â© 2018, Â© 2018 Informa UK Limited, trading as Taylor & Francis Group.